If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 48 + 17y = 24y + 27 Reorder the terms: 48 + 17y = 27 + 24y Solving 48 + 17y = 27 + 24y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-24y' to each side of the equation. 48 + 17y + -24y = 27 + 24y + -24y Combine like terms: 17y + -24y = -7y 48 + -7y = 27 + 24y + -24y Combine like terms: 24y + -24y = 0 48 + -7y = 27 + 0 48 + -7y = 27 Add '-48' to each side of the equation. 48 + -48 + -7y = 27 + -48 Combine like terms: 48 + -48 = 0 0 + -7y = 27 + -48 -7y = 27 + -48 Combine like terms: 27 + -48 = -21 -7y = -21 Divide each side by '-7'. y = 3 Simplifying y = 3
| 12x^4-28x^2-24=0 | | 4(2y+2)+10=6(5y+4)-19 | | 10=4c+8 | | 3z-26+2z=z+50 | | (2y-20)+(2y-20)+y=360 | | 7x-5x+8x+7x=180 | | 5(6x+2)=6(3x+3) | | 5x+6(-x+14)=74 | | 7(x+9)+2=-8(x-3)-6 | | -3m-2=-14 | | (3x-1)^3/8 | | (2y-20)+(2y-20)+y=180 | | 4(6x+1)=6(2x+4) | | 9x-13y=32 | | -6.6h=26.4 | | 5(2)+10R-25=250 | | (11+y)-6y=11 | | 8.00(4.00+72)=x | | x+26+47=7x-6 | | 3(2x-2)=4(6x-3) | | 20a+20b+3c+4c-5b-2a= | | 15x+18=3(x+5+4x) | | 5=-6.4+z | | 7y-4+31=9y | | 4(5y+3)+14=2(6y+2)+5 | | (11+x)-6y=11 | | 2x-14/4x | | 7x+44+x+31=16x | | 3t+17+50=10t-38 | | 15x+21y=53 | | 14.8=-3.7y | | 4x^2+7x-11=-11 |